2001
DOI: 10.1046/j.1365-2567.2001.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic characterization of human CD8+ T cells with natural killer cell markers in comparison with natural killer cells and normal CD8+ T cells

Abstract: SUMMARY+ T cells>CD57 + T cellsiCD8 + T cellsiNK cells. However, the CD3-stimulated proliferation of both NK-type T cells was smaller than that of CD8 + T cells partly because NK-type T cells were susceptible to apoptosis. In addition to NK cells, NK-type T cells but not CD8+ T cells stimulated with cytokines, expressed cytoplasmic perforin and granzyme B. Furthermore, CD3-stimulated IFN-c production from peripheral blood mononuclear cells (PBMC) correlated with the proportions of CD57 + T cells in PBMC from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
139
2
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(151 citation statements)
references
References 51 publications
9
139
2
1
Order By: Relevance
“…ϩ T cells [3,5], CD56 ϩ T cells were found to release higher levels of the Th1 cytokine, IFN-␥ than did similar numbers of CD56 Ϫ T cells. We found that the kinetics of IFN-␥ release were similar for both lymphocyte subsets, with maximal levels detectable after 48 hours.…”
Section: Cd56mentioning
confidence: 91%
See 2 more Smart Citations
“…ϩ T cells [3,5], CD56 ϩ T cells were found to release higher levels of the Th1 cytokine, IFN-␥ than did similar numbers of CD56 Ϫ T cells. We found that the kinetics of IFN-␥ release were similar for both lymphocyte subsets, with maximal levels detectable after 48 hours.…”
Section: Cd56mentioning
confidence: 91%
“…ϩ T cells belong to a heterogenous group of human T cells that express various stimulatory, costimulatory, inhibitory, and adhesion receptors that control NK cell activity [3][4][5][33][34][35]. T cells with NKRs, including CD56 ϩ T cells, are often present in cultures of stimulated T cells [4,11,[13][14][15][16][17], and they frequently express memory phenotypes [2,36,37].…”
Section: Cd56mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, CD56 + T cells have shown the capacity to produce both type 1 and type 2 cytokines 10,[15][16][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have defined CD8 þ T cells with expression of CD57 as replicatively scenescent T cells, 19 whereas others demonstrate these cells to be effector cytotoxic T cells that are increased in infections or neoplasms and represent a chronically activated state. [20][21][22][23][24] Still, others have shown that expansions of CD8 þ /CD57 þ T cells are seen with increased frequency in the elderly, and they have postulated defects in immune system homeostasis leading to expansion of these T cells and diminished immune system surveillance. 25 Nonetheless, we are not aware of significant studies on T cells with the phenotype of CD8 þ (dim)/CD57 þ expression.…”
Section: Discussionmentioning
confidence: 99%